Amorphous Calcium Phosphates: Solvent‐Controlled Growth and Stabilization through the Epoxide Route. Issue 39 (4th June 2021) - Borovik, Paula; Oestreicher, Víctor; Huck‐Iriart, Cristián; Jobbágy, Matías
Abstract: Calcium phosphates stand among the most promising nanobiomaterials in key biomedical applications, such as bone repairment, signalling or drug/gene delivery. Their intrinsic properties as crystalline structure, composition, particle shape and size define their successful use. Among these compounds, metastable amorphous calcium phosphate (ACP) is currently gaining particular attention due to its inherently high reactivity in solution, which is crucial in bone development mechanisms. However, the preparation of this highly desired (bio)material with control over its shape, size and phase purity remains as a synthetic challenge. In this work, the epoxide route was adapted for the synthesis of pure and stable ACP colloids. By using biocompatible solvents, such as ethylene glycol and/or glycerine, it was possible to avoid the natural tendency of ACP to maturate into more stable and crystalline apatites. Moreover, this procedure offers size control, ranging from small nanoparticles (60 nm) to micrometric spheroids (>500 nm). The eventual fractalization of the internal mesostructured can be tuned, by simply adjusting the composition of the ethylene glycol:glycerine solvent mixture. These findings introduce the use of green solvents as a new tool to control crystallinity and/or particle size in the synthesis of nanomaterials, avoiding the use of capping agents and preserving the natural chemical reactivity of the pristine surface. Abstract : Amorphous calcium phosphate (ACP) is a key nanobiomaterial where shape, size and phase purity remain as a synthetic challenge. Herein, we have adapted the Epoxide Route for the synthesis of pure and stable ACP colloids by using biocompatible solvents such as ethylene glycol and/or glycerine. The solvent mixture can be used as a new green tool to control the size (from 60 nm to >500 nm) and the internal mesostructured (fractal dimension).